First Nations : environmental knowledge and approaches to natural resources; methodological approach - University of Ottawa, Institute for Research on Environment and Economy (IREE) (University of Ottawa, Ottawa, ON, CA, 1994)
Contents: 1, Agenda 21 of the UNCED : assessment of chapter 26; recognizing and strengthening the role of indigenous people; 2, Methodology of community based development : socio-economic indicators and the native communities of Canada 3, Indigenous people and the environment : Canada government's approach